Beware of Nihilism: Favorable Outcome despite Poor Admission Status in Posterior Circulation Aneurysms after Aneurysmal Subarachnoid Hemorrhage - Brawanski, Nina; Kashefiolasl, Sepide; Won, Sae-Yeon; Berkefeld, Joachim; Hattingen, Elke; Senft, Christian; Seifert, Volker; Konczalla, Juergen (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Objective As shown in a previous study, aneurysm location seems to influence prognosis in patients with subarachnoid hemorrhage (SAH). We compared patients with ruptured aneurysms of anterior and posterior circulation, undergoing coil embolization, concerning differences in outcome and prognostic factors.Methods Patients with SAH were entered into a prospectively collected database. We retrospectively identified 307 patients with aneurysms of the anterior circulation (anterior cerebral artery, carotid bifurcation, and middle cerebral artery) and 244 patients with aneurysms of the posterior circulation (aneurysms of the basilar artery, posterior inferior cerebellar artery, posterior communicating artery and posterior cerebral artery). All patients underwent coil embolization. The outcome was assessed using the modified Rankin Scale (mRS; favorable [mRS 0–2] vs. unfavorable [mRS 3–6]) 6 months after SAH.Results In interventionally treated aneurysms of the anterior and posterior circulation, statistically significant risk factors for poor outcome were worse admission status and severe cerebral vasospasm. If compared with patients with ruptured aneurysms of the anterior circulation, patients with aneurysms of the posterior circulation had a significantly poorer admission status, and suffered significantly more often from an early hydrocephalus. Nonetheless, there were no differences in outcome or mortality rate between the two patient groups.Conclusion Patients with a ruptured aneurysm of the posterior circulation suffer more often from an early hydrocephalus and have a significantly worse admission status, possibly related to the untreated hydrocephalus. Nonetheless, the outcome and the mortality rate were comparable between ruptured anterior and posterior circulation aneurysms, treated by coil embolisation. Therefore, despite the poorer admission status of patients with ruptured posterior circulation aneurysms, treatment of these patients should be considered.
Keywords: aneurysm location; outcome; prognostic factor; subarachnoid hemorrhage